Comparison between two cultivars of longan fruit cv. 'Dongbi' and 'Fuyan' in the metabolisms of lipid and energy and its relation to pulp breakdown. (1st January 2023) - Lin, Yifen; Lin, Lijuan; Lin, Yixiong; Lin, Mengshi; Ritenour, Mark A.; Lin, Hetong
Highlights: 'Dongbi' longan had better pulp quality and a lower pulp breakdown index than 'Fuyan' 'Dongbi' longan had higher levels of PC, PI, U/S, IUFA, and USFA than 'Fuyan' 'Dongbi' longan had lower levels of AMP, PA, SFA, PLD, lipase, and LOX than 'Fuyan' 'Dongbi' longan had higher ATP, energy charge, and ATPase activity than 'Fuyan' Lower pulp breakdown of 'Dongbi' longan was due to lower lipid and energy metabolisms. Abstract: This work studied the difference in pulp breakdown between two cultivars of longan cv. 'Dongbi' and 'Fuyan' from the aspect of metabolisms of lipid and energy. The results reflected that, compared to 'Fuyan' longan, 'Dongbi' longan had higher levels of energy charge, U/S and IUFA, and higher amounts of USFA, PC, PI, ATP and ADP. Moreover, 'Dongbi' longan exhibited lower levels of SFA, PA, AMP and cell membrane permeability. Also, lower PLD, LOX and lipase activities, but higher ATPase activity, lower pulp breakdown index, and better pulp appearance were exhibited in 'Dongbi' longan. These data revealed that the mitigated pulp breakdown in 'Dongbi' longan was due to the comprehensive coordination of metabolisms in lipid and energy through maintaining a higher level of energy, a higher unsaturation degree of fatty acids, delaying the degradation of phospholipids, and better retaining the membrane structural integrity of microsome and entire cell.